STRATEGI POLITIK PARTAI GERINDRA PADA PEMILIHAN LEGISLATIF KABUPATEN BOGOR TAHUN 2019 - Elsa Putri Lestari, (2023)
After the reform era, a multiparty system was implemented in Indonesia which resulted in the emergence of many parties and the competition for power became very strict. In the current multiparty era, marketing politics is an inevitable necessity, including the Gerindra Party which was able to win political contestation in the 2019 Bogor Regency legislative election. This research uses the concept of political parties, political strategy and legislative elections which are explained by marketing politics and employs a qualitative method with a descriptive analytical type of research which aims to describe the tendency or reality that exists. The research findings shows that Gerindra Bogor Regency employs an approach towards Islamic religious figures and aligns its party with those close to Islam, as a political marketing strategy carried out through political activities by promoting candidates as products (products) through the use of media and socialization (promotion), calculating funds and the image of candidates (price) and making strategy dissemination in various regions (place). Before carrying out the 4P, Gerindra Bogor Regency conducted segmentation, targeting and positioning to maximize the 4P so that it could win the 2019 Bogor Regency Legislative Election.